Gigahertz free-space electro-optic modulators based on Mie resonances - Ileana-Cristina Benea-Chelmus; Sydney Mason; Maryna L. Meretska; Delwin L. Elder; Dmitry Kazakov; Amirhassan Shams-Ansari; Larry R. Dalton; Federico Capasso (Nature Communications, 2022)
Active photonics in free space is important in computing, imaging and sensing. Here, hybrid silicon-organic nanoscale structures change the intensity of a free-space light beam by applied microwave signals at gigahertz speeds with a high efficiency.